Study guide [for] Management accounting : a strategic approach - Morse, Wayne J.; Hartgraves, Al L.; Senge, Stephen V.; Davis, James R., 1936- (Cincinnati, OH : South-Western College, 2000)
This book is about: Management accounting; Activity cost analysis and planning; Contribution analysis for decision making; ...
Keywords: Accounting; Management; Managerial accounting